Evaluation of Visual Inspection of Cervix with Acetic Acid and Liquid Based in Cervical Cancer Screening with Cervical Biopsy - Shrestha, Bigya; Malla Vaidya, Karishma; Joshi, Rijuta (Journal of Nepal Health Research Council, 2020)
Background: Cervical cancer is the second most common cancer among women in developing countries. Cervical cancer generally develops slowly over a period of 10-15 years. Incidence and mortality related to cervical cancer both have declining in developed countries because of effective screening programs through Papanicolaou smear. Therefore, cervical cancer can be prevented through implementation of different methods of screening programs like visual inspection of cervix with application of acetic acid visual inspection with acetic acid, liquid based cytology and human papilloma virus deoxyribonucleic acid. The purpose of this study is to compare the efficacy of visual inspection with Acetic Acid with liquid based cytology in cervical cancer screening taking cervical biopsy as a gold standard. Methods: The study was conducted at Paropakar Maternity and Women’s Hospital, Kathmandu. One hundred forty four patients underwent visual inspection with acetic acid and liquid based cytology test followed by biopsy for confirmation of the lesion, when required. Data were obtained and statistically analyzed. Results: Out of 144 screened patients, 62 (43.05%) were positive in visual inspection with acetic acid test. Eighteen (12.5%) cases were positive in liquid based cytology. Thirteen women were positive with both tests. Thirty-nine cases underwent histopathological examination including 13 cases who were positive in both tests. The sensitivity, specificity, positive predictive value and negative predictive value for visual inspection with acetic acid was 81.25%, 65.22%, 61.90% and 83.33%, whereas for liquid based cytology it was 100%, 91.30%, 88.89% and 94.87% respectively. Conclusions: Liquid based cytology was more efficacious to diagnose atypical cells with higher sensitivity and specificity in comparison to that of visual Inspection with Acetic Acid test. Keywords: Cervical cancer; liquid based cytology; visual inspection with acetic acid